The Role of PNA General Public Budget as A mean for Planning and Controlling in Rationalizing Financial Decision - Qabaha, Mahmoud Gawdat; Moussa, Nael Adel (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the role of the Palestinian National Authority’s public budget as a tool for planning and control in making financial decisions, and the extent to which the PNA ministries and agencies rely on the budget as a tool for planning and control, and its role in rationalizing financial decisions, and to know whether there are difficulties facing decision-makers in ministries and agencies in the Palestinian National Authority limit the effectiveness of using budgets as a tool for planning and control and analytical approach was used for its suitability for the purposes of the study After collecting and analyzing secondary data, a questionnaire was designed as another tool for the study to answer the study questions and test its hypotheses. The questionnaire was distributed to a stratified random sample of 120 employees working in the ministries and authorities of the Palestinian National Authority. 104 questionnaires were retrieved, a percentage of A recovery amounted to (86.6%), which is a good percentage that satisfies the purposes of analysis, coming up with results and circulating them. One of the most important findings of the study is that the rationalization of financial decisions depends on control and not on planning, and that control has a fundamental role in following up the activities of the ministry or authority financially, which helps reduce the waste of public money allocated for the purposes of meeting the needs of public expenditures and some public service projects, as well as control on public revenues and strengthening its role in covering public expenditures. Based on these results, the study recommended the application of balancing programs and performance instead of balancing the applicable items, due to their relevance to a specific goal for each program. It also recommended holding periodic meetings for financial directors in each ministry or agency to study deviations in the budget and their causes, making feedback and increasing attention to human elements responsible for budget preparation and follow-up to develop professional and technical capabilities in using the general budget for better planning and control purposes through holding periodic meetings that contribute to deepening the dimensions of budget preparation.